2013
DOI: 10.1093/hmg/ddt549
|View full text |Cite
|
Sign up to set email alerts
|

Methionine sulfoxide reductase B3 deficiency causes hearing loss due to stereocilia degeneration and apoptotic cell death in cochlear hair cells

Abstract: Methionine sulfoxide reductase B3 (MsrB3) is a protein repair enzyme that specifically reduces methionine-R-sulfoxide to methionine. A recent genetic study showed that the MSRB3 gene is associated with autosomal recessive hearing loss in human deafness DFNB74. However, the precise role of MSRB3 in the auditory system and the pathogenesis of hearing loss have not yet been determined. This work is the first to generate MsrB3 knockout mice to elucidate the possible pathological mechanisms of hearing loss observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 31 publications
1
49
0
Order By: Relevance
“…Therefore, even though one member of the Msr protein family is not expressed, other Msr proteins will compensate its function. In addition, we recently reported that MsrB3 was expressed especially in cochlear hair cells, and MsrB3 − / − mice showed profound hearing loss [Kwon et al, 2014]. However, MsrB3 − / − mice did not show abnormal vestibular behavior, such as circling or head tossing, despite wild-type expression of MsrB3 in the hair cells of the crista ampullaris, utricle and saccule in the vestibule [Kwon et al, 2014].…”
Section: +mentioning
confidence: 97%
See 2 more Smart Citations
“…Therefore, even though one member of the Msr protein family is not expressed, other Msr proteins will compensate its function. In addition, we recently reported that MsrB3 was expressed especially in cochlear hair cells, and MsrB3 − / − mice showed profound hearing loss [Kwon et al, 2014]. However, MsrB3 − / − mice did not show abnormal vestibular behavior, such as circling or head tossing, despite wild-type expression of MsrB3 in the hair cells of the crista ampullaris, utricle and saccule in the vestibule [Kwon et al, 2014].…”
Section: +mentioning
confidence: 97%
“…In addition, we recently reported that MsrB3 was expressed especially in cochlear hair cells, and MsrB3 − / − mice showed profound hearing loss [Kwon et al, 2014]. However, MsrB3 − / − mice did not show abnormal vestibular behavior, such as circling or head tossing, despite wild-type expression of MsrB3 in the hair cells of the crista ampullaris, utricle and saccule in the vestibule [Kwon et al, 2014]. In this study, we also found MsrB1 expression especially in the hair cells of the crista ampullaris, utricle and saccule in the vestibule.…”
Section: +mentioning
confidence: 99%
See 1 more Smart Citation
“…Detection of methionine sulfoxide was performed with the methionine sulfoxide immunoblotting kit (Cayman, Ann Arbor, MI) according to the manufacturer's protocol (28,45). The details are provided in the Supplementary Methods section.…”
Section: Methionine Sulfoxide Assaymentioning
confidence: 99%
“…Methionine-R-sulfoxide reductase B3 (MSRB3) acts as an oxidoreductase, and its expression is only observed in hair, spiral ganglion, and inner phalangeal cell and Border and Deiters' cells. [65][66][67][68][69][70][71][72] Mutations in MSRB3 cause DFNB74, [65][66][67][68][69][70][71][72] revealing the importance of decreasing oxidative stress in the protection of hair and nerve cells. In contrast, many types of myosin and stereocillia components are not expressed in inner phalangeal, border, or Deiters' cells.…”
Section: Pillar Cells Are Anchors For the Basilar Membrane And Hair Cmentioning
confidence: 99%